Extensive Actinomycetoma Clinical Manifestations and Histopathology: A Case Report - Fifa Argentina; Rusmawardiana; Nopriyati; Putri Laksmi Karim (HM Publisher, 2022)
Background: Actinomycetoma is a chronic infection of cutis, subcutaneous, bone, and viscera tissue. It is characterized by sinuses containing masses of causative organisms often referred to as